Spatiotemporal Dynamics of 20th-Century Spruce Budworm Outbreaks in Eastern Canada: Three Distinct Patterns of Outbreak Severity - Berguet, Cassy; Martin, Maxence; Arseneault, Dominique; Morin, Hubert (Frontiers in Ecology and Evolution, 2021)
Spruce budworm (SBW) outbreaks are a major disturbance in North American forests. In Quebec, Canada, the recent history of SBW outbreaks at the local scale is well known. Studies at the Québec scale nonetheless remain rare despite the need to better understand the dynamics of SBW outbreaks at a larger scale. This study aimed to reconstruct the spatiotemporal dynamics of SBW outbreaks during the 20th century across the insect’s range in southern Quebec. To this end, we sampled 83 stands throughout southern Quebec. These stands were selected according to their age and the presence of black, white, and red spruce. In fact, spruce, unlike balsam fir, survives the SBW outbreaks and can record them in these growth rings. In each stand, cores were taken from 20 spruce trees. The dendrochronological series of more than 1600 trees were analyzed, and we identified, through the k-means grouping of stands, the spatial patterns of tree growth for the three previously documented 20th century SBW outbreaks. The outbreaks were not homogeneous across the distribution range of the insect. Two groups of stands showed early- (1905-1930) and late-century (1968-1988) outbreaks of high severity and a mid-century (1935-1965) outbreak of moderate severity. This pattern is explained mainly by the presence of the insect within the balsam fir–yellow birch and balsam fir–white birch bioclimatic domains, areas where outbreaks tend to be most severe because of the abundance of balsam fir, the main SBW host species. However, these two models differ in terms of the duration of outbreaks. A third, more northern, cluster of stands experienced lower severity outbreaks over the 20th century, a pattern explained by a lower proportion of balsam fir trees in these landscapes. Our study shows that, on the one hand, these three groups of stands are defined by outbreaks of specific duration (an outbreak period beginning when more than 20% of the trees are affected and ending when less than 20% of the trees are affected) and severity (in terms of percentage of affected trees), and on the other hand they are spatially distinct and subject to different climatic conditions.